High-voltage medium-nickel positive electrode material with in-situ coating layer, preparation method and application of high-voltage medium-nickel positive electrode material
Through the in situ wet method and the solid -phase high -temperature sintering process, the nickel positive pole material in high -voltage electricity is prepared to solve the problem of high cobalt content and unstable structure in existing materials, realizing high -voltage cycle stability and comparison High ratio capacity.
Patent Information
- Application Number
- CN202411483735.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-01-28
AI Technical Summary
The high cobalt content in the existing medium nickel ternary material preparation process leads to high material costs. At the same time, the material structure is unstable during high voltage cycles, which is prone to thermal runaway and electrolyte penetration.
The in situ wet method is used to cover the process, and the multi -solid -state electrolyte LATP and LLZO composite covering, combined with the solid -phase high -temperature sintering process, prepare medium nickel positive materials with high -voltage performance.
Achieve the stability of the material structure under high voltage 2.8-4.45V, improve the capacity and cycle stability of the material, and reduce the cost of material.
Smart Images

Figure CN119381430A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a high voltage nickel positive electrode material with an in-situ coating layer, a preparation method and an application thereof. Background Art
[0002] With the rapid development of China's economy and the increasing demand for new battery materials in the information age, China's new battery material market will continue to expand. Compared with commercial cathode materials such as lithium cobalt oxide, lithium iron phosphate, and lithium manganese oxide, nickel-cobalt-manganese ternary materials have higher gram capacity, better rate performance, and high and low temperature stability. With the comprehensive advantages of stable voltage, high capacity, large tap density, and high energy density, it has expanded its market share in battery cathode materials year by year and has been widely used. At the same time, market segmentation based on the characteristics and advantages of ternary materials can meet the customer requirements of market segments with different uses.
[0003] Currently, the more mature conventional medium-nickel ternary materials on the market are 523 and 622 ternary materials, but the existing preparation processes require a higher content of cobalt. Cobalt is one of the important positive electrode materials in ternary lithium batteries, but the resource is scarce. The price has continued to rise since 2017. The high price of cobalt has led to high material costs. On the one hand, the price of cobalt has continued to rise, and on the other hand, subsidies have gradually withdrawn, restricting the market expansion of ternary materials.
[0004] At the same time, high-nickel ternary positive electrode materials include 8 series and 9 series. Although they are high-energy-density lithium-ion battery materials, they also have many technical difficulties. Specifically: (1) Safety: During charging and discharging, oxygen in the lattice will escape, resulting in structural damage, decreased cycle performance, poor thermal stability, easy thermal runaway, and increased safety hazards; (2) Surface instability: The surface of high-nickel ternary materials is prone to side reactions with air, water, electrolyte, etc. to form an inert layer. Cation mixing will reduce the specific capacity and cycle stability of the material; (3) Microcracks: Due to the multivalent nature and volume changes of nickel ions, strain and microcracks are easily generated in secondary particles. Microcracks will accelerate electrolyte penetration and transition metal dissolution; (4) The process conditions are harsh, and the difficulty of preparation is significantly increased relative to medium nickel.
[0005] In summary, it is necessary to develop a high-voltage medium nickel single crystal 6-series positive electrode material. Summary of the invention
[0006] The technical problem to be solved by the present invention is to overcome the defects of the prior art. The present invention proposes a high-voltage nickel positive electrode material with an in-situ coating layer, a preparation method and an application thereof, in order to ensure that the nickel single crystal 613 positive electrode material has a high specific capacity (can be on par with 8 series products) in the high voltage (room temperature charging and discharging 2.8-4.45V) and also to ensure that during the high voltage cycle, the Li ion embedding and extraction, the H2-H3 phase change caused by the valence change of Ni, Co, and Mn ions during the oxidation-reduction process and many other factors are maintained while maintaining the stability of the material structure.
[0007] In order to solve the above technical problems, the technical solution adopted by the present invention is: a method for preparing a nickel positive electrode material for high voltage electricity with an in-situ coating layer, comprising the following steps:
[0008] S1. Obtaining a primary material for a medium-nickel positive electrode: mixing a nickel-cobalt-manganese hydroxide precursor with a lithium source, and then performing solid-phase high-temperature sintering. The obtained material is subjected to air flow crushing to obtain a primary material for a medium-nickel positive electrode;
[0009] S2. preparing an in-situ wet coating agent: diluting an oily coating agent with N-methylpyrrolidone to obtain an in-situ wet coating agent, wherein the oily coating agent comprises 4 wt % of lithium aluminum titanium phosphate and 4 wt % of lithium lanthanum zirconate, wherein the lithium aluminum titanium phosphate and the lithium lanthanum zirconate are dissolved in methyl methacrylate;
[0010] S3, in-situ wet coating: adding the nickel-nickel cathode primary material into the in-situ wet coating agent, stirring for 3 hours in a water bath at 10° C., and filtering to obtain a muddy solid;
[0011] S4. Preparation of a medium nickel positive electrode material with in-situ coating: sintering the obtained muddy solid to obtain a medium nickel positive electrode material with in-situ coating.
[0012] Furthermore, in S1, the molar ratio of the lithium source to the nickel-cobalt-manganese hydroxide precursor is 1.05-1.08:1, and the nickel content in the nickel-cobalt-manganese hydroxide is 0.6-0.65.
[0013] Furthermore, the solid-phase high-temperature sintering process includes multiple sintering processes: the mixed material is gradually heated to 400°C at room temperature and calcined for 2 hours, then gradually heated to 700°C and calcined for 2 hours, and finally heated to 930°C and calcined for 10 hours, and then the material is annealed and collected.
[0014] Furthermore, the particle size D50 of the nickel-cobalt-manganese hydroxide is 3.0-4.5 μm, and the particle size D50 of the nickel positive electrode primary material is 3.5-5.0 μm after air flow crushing control.
[0015] Furthermore, in S4, the muddy solid is subjected to primary sintering and secondary sintering in sequence to obtain a medium nickel positive electrode material with in-situ coating.
[0016] Furthermore, the primary sintering process is specifically as follows: the muddy solid is calcined at 130° C. for 5 hours and then cooled to room temperature, and directly sieved through 400 mesh and collected.
[0017] Furthermore, the secondary sintering process is as follows: the material obtained after the primary calcination is gradually heated to 600°C at room temperature, the heating rate is 2°C / min, the calcination lasts for 6 hours, then the temperature is lowered to room temperature and the obtained material is collected to obtain a medium nickel positive electrode material with in-situ coating. The secondary high-temperature sintering can fully decompose MMA and remove it from the primary positive electrode material. At the same time, LATP and LLZO react with the primary material at high temperature to play a role of full coating. The conductivity of the material can be improved after coating. At the same time, the structural stability of the positive electrode material can also be improved by introducing substances such as Al, Ti, La, and Zr contained in the coating agent into the material.
[0018] Furthermore, a nickel positive electrode material for high voltage electricity with an in-situ coating layer is prepared according to a method for preparing a nickel positive electrode material for high voltage electricity with an in-situ coating layer.
[0019] Furthermore, a lithium-ion battery is provided, the lithium-ion battery comprising a high-voltage nickel positive electrode material with an in-situ coating layer.
[0020] Compared with the prior art, the beneficial effects of the present invention include:
[0021] 1) Through multiple solid electrolytes LATP and LLZO composite coating, and using in-situ wet process to improve the coating effect, using oily organic solvents to avoid the damage of aqueous solvents to the material structure; using diluent NMP to dilute the oily coating agent in a certain proportion to prepare an in-situ wet coating agent. The addition of NMP can help adjust the viscosity of the oily coating agent and help the dispersion uniformity of the solid electrolyte in the system;
[0022] 2) Using a precursor nickel-cobalt-manganese hydroxide with a nickel content of 0.60≤x≤0.65, the precursor is a single crystal particle, ensuring that the corresponding positive electrode primary material is a single crystal structure; the size effect of the single crystal structure particles provides a structural stability foundation for the subsequent electrical performance;
[0023] 3) The positive electrode material after in-situ wet coating is more uniform, which improves the material conductivity. The Al, Ti, La, Zr and other substances introduced by the coating agent can also improve the structural stability of the positive electrode material. Better material conductivity and higher structural stability can make LiNi 0.60≤x≤0.65 Co y Mn 1-x-yThe O2 material is charged and discharged at a high voltage of 2.8-4.45V, achieving better electrical properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] The disclosure of the present invention is described with reference to the accompanying drawings. It should be understood that the drawings are for illustrative purposes only and are not intended to limit the scope of protection of the present invention. In the accompanying drawings, the same reference numerals are used to refer to the same components. Among them:
[0025] Figure 1 Schematic showing the steps of preparing high voltage nickel cathode material with in-situ coating layer;
[0026] Figure 2 Schematic diagram showing the in-situ wet coating preparation of LiNi 0.60 Co 0.10 Mn 0.30 SEM image of O2 cathode material;
[0027] Figure 3 Schematic diagram showing the solid phase hybrid coating preparation of LiNi 0.60 Co 0.10 Mn 0.30 SEM image of O2 positive electrode material. DETAILED DESCRIPTION
[0028] It is easy to understand that according to the technical solution of the present invention, without changing the essential spirit of the present invention, a person skilled in the art can propose a variety of interchangeable structural modes and implementation modes. Therefore, the following specific implementation modes and drawings are only exemplary descriptions of the technical solution of the present invention, and should not be regarded as the whole of the present invention or as a limitation or restriction to the technical solution of the present invention.
[0029] A method for preparing a high-voltage nickel positive electrode material with an in-situ coating layer comprises the following steps:
[0030] S1. Obtaining a primary material for a medium-nickel positive electrode: After mixing a nickel-cobalt-manganese hydroxide precursor with a lithium source, solid-phase high-temperature sintering is performed, and the mixed material is gradually heated to 400°C at room temperature and calcined for 2 hours, then gradually heated to 700°C and calcined for 2 hours, and finally heated to 930°C and calcined for 10 hours, annealing and collecting the material, and the obtained material is subjected to air flow crushing to obtain a primary material for a medium-nickel positive electrode;
[0031] S2. preparing an in-situ wet coating agent: diluting an oily coating agent with N-methylpyrrolidone to obtain an in-situ wet coating agent, wherein the oily coating agent comprises 4 wt% of lithium aluminum titanium phosphate and 4 wt% of lithium lanthanum zirconate, wherein the lithium aluminum titanium phosphate and the lithium lanthanum zirconate are dissolved in methyl methacrylate;
[0032] S3, in-situ wet coating: add the nickel-nickel cathode primary material to the in-situ wet coating agent, stir for 3 hours in a water bath at 10°C, and filter to obtain a muddy solid; the in-situ wet coating of the nickel-nickel cathode primary material is adopted. It is obviously different from the solid phase mixing coating process. If the solid phase mixing is used, there is the disadvantage of slight uneven coating; the solubility of Li ions can be effectively reduced at low temperatures to ensure that less Li ions in the primary material are dissolved in the solution;
[0033] S4, preparing a medium nickel positive electrode material with in-situ coating: sintering the obtained muddy solid to obtain a medium nickel positive electrode material with in-situ coating; the aforementioned sintering process includes primary sintering and secondary sintering;
[0034] The primary sintering process is as follows: the muddy solid is calcined at 130° C. for 5 hours, then cooled to room temperature, and directly sieved through 400 mesh and collected;
[0035] The secondary sintering process is as follows: the material obtained after the primary calcination is gradually heated to 600°C at room temperature, with a heating rate of 2°C / min. After calcination for 6 hours, it is cooled to room temperature and the obtained material is collected to obtain a medium nickel positive electrode material with in-situ coating. The secondary high-temperature sintering can fully decompose MMA and remove it from the primary positive electrode material. At the same time, LATP and LLZO react with the primary material at high temperature to play a role in full coating. The conductivity of the material can be improved after coating. At the same time, the structural stability of the positive electrode material can also be improved by introducing substances such as Al, Ti, La, and Zr contained in the coating agent into the material.
[0036] Embodiment 1
[0037] A high-voltage medium-nickel positive electrode material with an in-situ coating layer, a preparation method and its application. The medium-nickel positive electrode material is a lithium battery ternary nickel-cobalt-manganese oxide, namely, lithium nickel-cobalt-manganese oxide, and its chemical formula is: LiNi 0.60≤x≤0.65 Co y Mn 1-x-y O2. First, a precursor nickel cobalt manganese hydroxide with a nickel content of 0.60 was used, and its particle size D50: 3.8μm. After mixing the lithium source and the precursor at a molar ratio of 1.06:1, solid-phase high-temperature sintering was performed at 930°C for 10 hours. The material was annealed and collected, and the particle size D50: 4.0μm was controlled by air flow crushing to obtain a medium nickel positive electrode primary material.
[0038] Furthermore, the in-situ wet coating process is used to treat and coat the primary material of the medium nickel positive electrode. Specifically: using methyl methacrylate MMA as an organic solvent, weighing lithium aluminum titanium phosphate (LATP) accounting for 4wt% of the mass ratio of MMA and lithium lanthanum zirconate (LLZO) accounting for 4wt% of the mass ratio of MMA, adding them to methyl methacrylate MMA, and fully mixing them to form a solid electrolyte oily coating agent with a total content of 8wt%. Then use the diluent N-methylpyrrolidone NMP to dilute the oily coating agent from the original 8wt% to 5% to prepare an in-situ wet coating agent. Take a certain mass of 1000g of the primary material of the medium nickel positive electrode, add it to the diluted in-situ wet coating agent, stir it at a low temperature of 10℃ in a water bath for 3h, filter out the NMP liquid, and then calcine the muddy solid in an environment of 130℃ for the first time, calcine for 5h to room temperature, directly sieve 400 mesh, and then sinter it for a second time at 600℃ for 6h, 2℃ / min. Finally, the medium nickel LiNi with in-situ coating was obtained. 0.60 Co 0.10 Mn 0.30 O2 positive electrode finished product.
[0039] Embodiment 2
[0040] A high-voltage nickel positive electrode material with an in-situ coating layer, a preparation method and an application thereof. The difference from the first embodiment is that a precursor nickel-cobalt-manganese hydroxide with a nickel content of 0.65 is used.
[0041] Embodiment 3
[0042] A high-voltage medium-nickel positive electrode material with an in-situ coating layer, a preparation method and an application thereof. The difference from Example 1 is that 3 wt% of lithium aluminum titanium phosphate (LATP) and 3 wt% of lithium lanthanum zirconate (LLZO) are weighed and added to methyl methacrylate (MMA).
[0043] Embodiment 4
[0044] A high-voltage nickel positive electrode material with an in-situ coating layer, a preparation method and an application thereof. The difference from Example 1 is that 5wt% of lithium aluminum titanium phosphate (LATP) and 5wt% of lithium lanthanum zirconate (LLZO) are weighed and added into methyl methacrylate (MMA).
[0045] Embodiment 5
[0046] A high-voltage nickel positive electrode material with an in-situ coating layer, a preparation method and an application thereof. The difference from the first embodiment is that the oily coating agent is diluted by a diluent N-methylpyrrolidone NMP to a certain ratio from the original 8wt% to 4%, thereby preparing an in-situ wet coating agent.
[0047] Embodiment 6
[0048] A high-voltage nickel positive electrode material with an in-situ coating layer, a preparation method and an application thereof. The difference from the first embodiment is that the oily coating agent is diluted by a diluent N-methylpyrrolidone NMP to a certain ratio from the original 8wt% to 6%, thereby preparing an in-situ wet coating agent.
[0049] Embodiment 7
[0050] A high-voltage medium-nickel positive electrode material with an in-situ coating layer, a preparation method and an application thereof. The difference from Example 1 is that 1000 g of a certain mass of medium-nickel positive electrode primary material is taken and added to the diluted in-situ wet coating agent, stirred at a low temperature of 15° C. in a water bath for 3 hours, and then the NMP liquid is filtered off.
[0051] Embodiment 8
[0052] A high-voltage medium-nickel positive electrode material with an in-situ coating layer, a preparation method and an application thereof. The difference from Example 1 is that 1000 g of a certain mass of medium-nickel positive electrode primary material is added to the diluted in-situ wet coating agent, stirred at a low temperature of 6° C. in a water bath for 3 hours, and then the NMP liquid is filtered off.
[0053] Embodiment 9
[0054] A high-voltage medium-nickel positive electrode material with an in-situ coating layer, a preparation method and an application thereof. The difference from Example 1 is that the muddy solid is initially calcined in an environment of 110° C., the calcination lasts for 5 hours, the temperature is cooled to room temperature, and the solid is directly sieved with 400 mesh.
[0055] Embodiment 10
[0056] A high-voltage medium-nickel positive electrode material with an in-situ coating layer, a preparation method and an application thereof. The difference from Example 1 is that the muddy solid is initially calcined in an environment of 150° C., the calcination lasts for 5 hours, the temperature is cooled to room temperature, and the solid is directly sieved with 400 mesh.
[0057] Embodiment 11
[0058] A high-voltage medium-nickel positive electrode material with an in-situ coating layer, a preparation method and an application thereof. The difference from the first embodiment is that a secondary sintering is performed at 550° C. for 6 hours and 2° C. / min.
[0059] Embodiment 12
[0060] A high-voltage medium-nickel positive electrode material with an in-situ coating layer, a preparation method and an application thereof. The difference from the first embodiment is that a secondary sintering is performed at 650° C. for 6 hours and 2° C. / min.
[0061] Embodiment 13
[0062] A high-voltage nickel positive electrode material with an in-situ coating layer, a preparation method and an application thereof. The difference from the first embodiment is that a secondary sintering is performed at 600° C. for 6 hours and 1° C. / min.
[0063] Embodiment 14
[0064] A high-voltage medium-nickel positive electrode material with an in-situ coating layer, a preparation method and an application thereof. The difference from the first embodiment is that a secondary sintering is performed at 600° C. for 6 hours and 3° C. / min.
[0065] Comparison sample
[0066] A high-voltage medium-nickel positive electrode material with an in-situ coating layer, a preparation method and its application. The medium-nickel positive electrode material is a lithium battery ternary nickel-cobalt-manganese oxide, namely, lithium nickel-cobalt-manganese oxide, and its chemical formula is: LiNi 0.60≤x≤0.65 Co y Mn 1-x-y O2. First, a precursor nickel cobalt manganese hydroxide with a nickel content of 0.60 was used, and its particle size D50: 3.8μm. After mixing the lithium source and the precursor at a molar ratio of 1.06:1, solid-phase high-temperature sintering was performed at 930°C for 10 hours. The material was annealed and collected, and the particle size D50: 4.0μm was controlled by air flow crushing to obtain a medium nickel positive electrode primary material.
[0067] Furthermore, a solid phase mixed coating process was used to sinter 4wt% lithium aluminum titanium phosphate (LATP) and 4wt% lithium lanthanum zirconate (LLZO) at 600℃ for 6h, 2℃ / min. Finally, a medium nickel LiNi with in-situ coating was obtained. 0.60 Co 0.10 Mn 0.30 O2 positive electrode finished product.
[0068] The above embodiment was assembled into a button-type half-cell for testing. The process of assembling the button-type half-cell is as follows: lithium half-cell model CR2032. The assembly order is: negative electrode shell, lithium sheet, electrolyte LiPF6, diaphragm sheet, positive electrode sheet described in this patent, gasket, spring, positive electrode shell.
[0069] (1) Capacity: The prepared battery was tested on a button battery test system at room temperature, with a charge and discharge voltage range of 2.8-4.45V, and the capacity of the battery was tested at 0.1C charge and discharge.
[0070] (2) Rate performance test: The prepared battery was tested on a button cell test system at room temperature, with a charge and discharge voltage range of 2.8-4.45V and the capacity at 0.1C, 1C, 2C, and 3C.
[0071] (3) Cycle performance test: The prepared battery was tested on a button cell test system at room temperature with a charge and discharge voltage range of 2.8-4.45 V. The battery was cycled for 100 cycles at a current density of 1 C to test the capacity retention rate.
[0072]
[0073]
[0074] pass Figure 2 The SEM image of the in-situ wet coating preparation shows that the coating agent of the prepared positive electrode material is evenly distributed on the surface of the particles without obvious micro-inhomogeneity.
[0075] pass Figure 3 The SEM image of the solid phase mixed coating preparation shows that the coating agent of the prepared positive electrode material is micro-aggregated, and there is no coating agent on the surface of some positive electrode materials, which has obvious micro-inhomogeneity.
[0076] Example 1 The positive electrode material prepared under the optimal conditions has an electrical performance capacity of 201.20 mAh / g, and after 100 cycles at 1C, the capacity retention rate reaches 91%, showing good electrical performance and high structural stability.
[0077] Example 2 is to adjust the original Ni content of Example 1 from 60% to 65%. The electrical properties of the two are almost the same, indicating that the nickel content range of 0.60≤x≤0.65 is more reasonable. However, as the Ni content increases, Li + / Ni 2+ The preferred Ni content of 60% is more reasonable.
[0078] In Example 3, lithium aluminum titanium phosphate (LATP) accounting for 3wt% of the mass ratio of MMA and lithium lanthanum zirconate (LLZO) accounting for 3wt% of the mass ratio of MMA are added to methyl methacrylate MMA and fully mixed to prepare a solid electrolyte oily coating agent with a total content of 6wt%. The total content of the solid electrolyte is relatively small, resulting in relatively small multi-ion conductors, which causes the particle size to be smaller than that of Example 1, and its capacity is reduced compared with Example 1.
[0079] Example 4 is to take 5wt% of lithium aluminum titanium phosphate (LATP) and 5wt% of lithium lanthanum zirconate (LLZO) by weight of MMA, add them to methyl methacrylate MMA, and mix them thoroughly to make a solid electrolyte oily coating agent with a total content of 10wt%. The total content of solid electrolyte is not the more the better. More multi-ion conductors will cause the Li transmission channel to be blocked, the impedance to increase, and the electrical performance to deteriorate.
[0080] In Example 5, the oily coating agent is diluted from 8wt% to 4% by using the diluent N-methylpyrrolidone NMP to prepare an in-situ wet coating agent. Compared with the dilution to 5% in Example 1, the dilution concentration is lower, because NMP will eventually be eliminated, leaving the coating agent content unchanged, but the change in dilution concentration brings about an increase in cost, and the electrical performance has no significant change compared with Example 1.
[0081] In Example 6, the oily coating agent was diluted from 8 wt % to 6 wt % by using N-methylpyrrolidone NMP to prepare an in-situ wet coating agent. Compared with the solution concentration of Example 1, the coating agent was slightly non-uniformly dispersed, resulting in lower electrical performance than that of Example 1.
[0082] In Example 7, 1000 g of a certain mass of a nickel-based primary cathode material was added to a diluted in-situ wet coating agent, stirred for 3 h at a low temperature of 15° C. in a water bath, and then the NMP liquid was filtered off. The water bath temperature was higher than that in Example 1. As the temperature increased, the solubility of Li increased, resulting in poor electrical performance.
[0083] In Example 8, 1000 g of a certain mass of a medium nickel positive electrode primary material is added to the diluted in-situ wet coating agent, stirred at a low temperature of 6° C. in a water bath for 3 h, and then the NMP liquid is filtered off. A relatively low temperature is conducive to reducing Li dissolution. Although the performance is the same as that of Example 1, the lower the temperature, the higher the cost and the higher the difficulty of preparation.
[0084] In Example 9, the muddy solid was initially calcined at 110° C., and the calcination lasted for 5 hours until the solid was cooled to room temperature, and then directly sieved through 400 mesh. At a relatively low temperature, a large amount of NMP remained, which affected the subsequent electrical performance.
[0085] In Example 10, the muddy solid is calcined at 150°C for the first time, and the calcination lasts for 5 hours until the temperature drops to room temperature, and the solid is directly sieved through 400 mesh. At relatively high temperatures, NMP can be removed well. Although the performance is the same as that of Example 1, the higher the temperature, the higher the cost and the higher the difficulty of preparation.
[0086] Example 11 is a secondary sintering at 550°C for 6h, 2°C / min. The sintering temperature is low, the layered structure is not crystallized enough, and the coating agent structure is unstable. Although the electrical performance is the same as that of Example 1 in the early stage, as the number of cycles increases, the electrical performance deteriorates due to structural instability.
[0087] Example 12 is a secondary sintering at 650° C. for 6 h, 2° C. / min. The sintering temperature is high, the layered structure is too dense, and the Li channel transmission is blocked, resulting in poor electrical performance and high cost.
[0088] Example 13 is a secondary sintering at 600°C for 6h, 1°C / min. The temperature gradient is small, which is equivalent to an increase in sintering strength. The layered structure is also too dense, and the Li channel transmission is blocked, which also leads to poor electrical performance and high cost.
[0089] Example 14 is a secondary sintering at 600°C for 6h, 3°C / min. As the temperature gradient increases, the layered structure reaction accelerates, the structure becomes relatively unstable, and the electrical properties deteriorate.
[0090] The technical scope of the present invention is not limited to the contents in the above description. Those skilled in the art can make various deformations and modifications to the above embodiments without departing from the technical idea of the present invention, and these deformations and modifications should all fall within the protection scope of the present invention.
Claims
1. A method for preparing a nickel positive electrode material for high voltage electricity with an in-situ coating layer, characterized in that: The steps include: S1. Obtaining a primary material for a medium-nickel positive electrode: mixing a nickel-cobalt-manganese hydroxide precursor with a lithium source, and then performing solid-phase high-temperature sintering. The obtained material is subjected to air flow crushing to obtain a primary material for a medium-nickel positive electrode; S2. preparing an in-situ wet coating agent: diluting an oily coating agent with N-methylpyrrolidone to obtain an in-situ wet coating agent, wherein the oily coating agent comprises 4 wt % of lithium aluminum titanium phosphate and 4 wt % of lithium lanthanum zirconate, wherein the lithium aluminum titanium phosphate and the lithium lanthanum zirconate are dissolved in methyl methacrylate; S3, in-situ wet coating: adding the nickel-nickel cathode primary material into the in-situ wet coating agent, stirring for 3 hours in a water bath at 10° C., and filtering to obtain a muddy solid; S4. Preparation of a medium nickel positive electrode material with in-situ coating: sintering the obtained muddy solid to obtain a medium nickel positive electrode material with in-situ coating.
2. The method for preparing a nickel positive electrode material for high voltage electricity with an in-situ coating layer according to claim 1, characterized in that: In S1, the molar ratio of the lithium source to the nickel-cobalt-manganese hydroxide precursor is 1.05-1.08:1, and the nickel content in the nickel-cobalt-manganese hydroxide is 0.6-0.
65.
3. The method for preparing a nickel positive electrode material for high voltage electricity with an in-situ coating layer according to claim 2, characterized in that: The solid phase high temperature sintering process includes multiple sintering processes: the mixed material is gradually heated to 400°C at room temperature and calcined for 2 hours, then gradually heated to 700°C and calcined for 2 hours, and finally heated to 930°C and calcined for 10 hours, and then the material is annealed and collected.
4. The method for preparing a nickel positive electrode material for high voltage electricity with an in-situ coating layer according to claim 3, characterized in that: The particle size D50 of the nickel-cobalt-manganese hydroxide is 3.0-4.5 μm, and the particle size D50 of the nickel positive electrode primary material is 3.5-5.0 μm after air flow crushing control.
5. The method for preparing a nickel positive electrode material for high voltage electricity with an in-situ coating layer according to claim 1, characterized in that: In S4, the muddy solid is subjected to primary sintering and secondary sintering in sequence to obtain a medium nickel positive electrode material with in-situ coating.
6. The method for preparing a nickel positive electrode material for high voltage electricity with an in-situ coating layer according to claim 3, characterized in that: The primary sintering process is specifically as follows: the muddy solid is calcined at 130° C. for 5 hours, then cooled to room temperature, and directly sieved through 400 mesh and collected.
7. The method for preparing a nickel positive electrode material for high voltage electricity with an in-situ coating layer according to claim 4, characterized in that: The secondary sintering process is as follows: the material obtained after the primary calcination is gradually heated to 600°C at room temperature, with a heating rate of 2°C / min. After calcination for 6 hours, it is cooled to room temperature and the obtained material is collected to obtain a medium nickel positive electrode material with in-situ coating.
8. A nickel positive electrode material for high voltage electricity with an in-situ coating layer, characterized in that: The method for preparing the nickel positive electrode material for high voltage electricity with an in-situ coating layer according to any one of claims 1 to 7 is used.
9. A lithium ion battery, characterized in that: The lithium-ion battery comprises the high-voltage nickel positive electrode material with an in-situ coating layer as claimed in claim 8.